Low IL7R Expression at Diagnosis Predicted Relapse in Adult Acute Myeloid Leukemia Patients With t(8;21) - Xu, Nan; Sun, Kai; Wang, Ya-Zhe; Chen, Wen-Min; Wang, Jun; Li, Ling-Di; Wang, Xu; Hao, Yue; Chang, Yan; Liu, Yan-Rong; Huang, Xiao-Jun; Qin, Ya-Zhen (Frontiers in Immunology, 2022)
Background: Acute myeloid leukemia (AML) with t(8;21) needs to be further stratified. In addition to leukemia cells, immune cells in tumor microenvironment participate in tumor initiation, growth and progression. Interleukins (ILs)/interleukin receptors (ILRs) interaction plays important roles in the antitumor immune response. IL7R is reported to be relevant to prognosis in solid tumor and acute lymphoblastic leukemia. However, the prognostic significance of IL7R in t(8;21) AML remains to be clarified. Methods: Bone marrows collected from 156 newly diagnosed t(8;21) AML patients were used for testing IL7R transcript level by TaqMan-based real-time quantitative PCR (RQ-PCR), and RNAseq were performed in 15 of them. Moreover, IL7R expression at diagnosis were measured by RQ-PCR and flow cytometry (FCM) simultaneously in other 13 t(8;21) AML patients. . Results: t(8;21) AML patients had varied IL7R transcript levels and were categorized into low-expression (IL7R-L) and high-expression (IL7R-H) groups; IL7R-L was significantly associated with a lower relapse-free survival (RFS) rate (P=0.0027) and KITD816/D820 mutation (P=0.0010). Furthermore, IL7R-L was associated with a lower RFS rate in KITD816/D820 group (P=0.013) and IL7R-H/KITD816/D820 patients had similar RFS to KITN822/e8/WT patients (P=0.35). GO analysis enrichment showed that down-regulated genes were predominantly involved in the regulation of T cell and leukocyte activation, proliferation and differentiation in IL7R-L group. IL7R-L had significantly lower levels of Granzymes A/B, CCR7, CD28 and CD27 than IL7R-H group (all P<0.05). FCM analysis showed IL7R protein was primarily expressed in CD4+ T and CD8+ T cell subset. A significant association was found between the transcript level of IL7R and the percentage of CD8+ T cells in nucleated cells (P=0.015) but not CD4+ T cells (P=0.47). Conclusion: Low IL7R transcript level of bone marrow at diagnosis predicted relapse in t(8;21) AML, which might be caused by the difference in the amount, status and function of T cells.